2016
DOI: 10.1016/j.ajhg.2016.04.011
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Sequencing Exploratory Research Consortium: Accelerating Evidence-Based Practice of Genomic Medicine

Abstract: Despite rapid technical progress and demonstrable effectiveness for some types of diagnosis and therapy, much remains to be learned about clinical genome and exome sequencing (CGES) and its role within the practice of medicine. The Clinical Sequencing Exploratory Research (CSER) consortium includes 18 extramural research projects, one National Human Genome Research Institute (NHGRI) intramural project, and a coordinating center funded by the NHGRI and National Cancer Institute. The consortium is exploring anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 108 publications
(137 reference statements)
1
81
0
Order By: Relevance
“…This finding may have been influenced by protocol differences across studies. If, how, and what types of secondary findings were disclosed greatly varied by study (Green et al 2016), for example, the Pediseq project allowed participants to opt out of secondary findings that were determined to be not immediately medically actionable (Berg et al 2013). Regardless, recent research indicates that the majority of individuals who pursue GS express interest in secondary findings (Shahmirzadi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding may have been influenced by protocol differences across studies. If, how, and what types of secondary findings were disclosed greatly varied by study (Green et al 2016), for example, the Pediseq project allowed participants to opt out of secondary findings that were determined to be not immediately medically actionable (Berg et al 2013). Regardless, recent research indicates that the majority of individuals who pursue GS express interest in secondary findings (Shahmirzadi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Enrollment in the other CSER projects took place between December 2011 and May 2016. More details about the CSER consortium and the individual site populations and goals, including information about the types of primary results reported by each CSER site and their reporting of secondary findings, are described elsewhere (Green et al 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical application of Next Generation Sequencing (NGS) has enhanced molecular profiling capacity (Kamps et al., 2017). NGS sequencing methods are now commonly used in personalized clinical cancer care (Chang et al., 2017; Green et al., 2016). However, NGS also yields increasing numbers of variants that predominantly are of unknown significance and compounds the challenge of variant interpretation (Good, Ainscough, McMichael, Su, & Griffith, 2014; Kamps et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrable impacts on diagnostic rates and treatment have already been shown across a broad range of specialties. [1][2][3][4] In order to achieve widespread implementation of genomic care, it will be necessary to alter care pathways to incorporate early genomic testing and then expand the delivery of genetic and genomic care beyond clinical genetics and into mainstream clinical specialties. [5][6][7] A recent review of genetic service models has suggested that multidisciplinary clinics and coordinated services are key to delivering proper care in rare genetic disorders.…”
Section: Introductionmentioning
confidence: 99%